SKETSA KESEHATAN REPRODUKSI REMAJA - Siti Hikmah Anas (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
When looking at the phenomenon in newspapers, magazines, and television, a lot of adolescent reproductive healthdisorder. This phenomenon is not without cause. Environmental factors, economic factors, and the most cause is the factor that they havelack of knowledge on reproductive health. Until now, knowledge about reproduction considered taboo. In fact, that statement has become amyth among the public. This paper tried to reveal the causes of adolescent reproductive health disorder, which on the other side trying toprovide solutions. This solution is very important to enlighten the knowledge and insight readers, especially young people about reproductivehealth disorders.